2020
DOI: 10.1161/circresaha.119.316394
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Flora Modulates Blood Pressure by Regulating the Synthesis of Intestinal-Derived Corticosterone in High Salt-Induced Hypertension

Abstract: Rationale: High-salt diet is one of the most important risk factors for hypertension. Intestinal flora has been reported to be associated with high salt–induced hypertension (hSIH). However, the detailed roles of intestinal flora in hSIH pathogenesis have not yet been fully elucidated. Objective: To reveal the roles and mechanisms of intestinal flora in hSIH development. Methods and Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 56 publications
2
112
0
1
Order By: Relevance
“…More recently, a novel mechanism different from inflammation or immunity regulation has been presented. In high salt-induced hypertensive mice, elevated blood pressure is closely related to increased levels of intestinal-derived corticosterone [ 72 ].…”
Section: Implications Of Gut Microbiota In Cvdsmentioning
confidence: 99%
“…More recently, a novel mechanism different from inflammation or immunity regulation has been presented. In high salt-induced hypertensive mice, elevated blood pressure is closely related to increased levels of intestinal-derived corticosterone [ 72 ].…”
Section: Implications Of Gut Microbiota In Cvdsmentioning
confidence: 99%
“…Our previous study firstly confirmed that transplants from hypertensive patient feces reshaped the gut microbiota of healthy GF mice and rendered significant BP elevation (9). Of note, modulating intestinal flora via transplantation from healthy rats could dramatically reduce BP in high salt-induced hypertensive animals (12). Oral antibiotics such as minocycline and vancomycin can assist on treatment of hypertension (13).…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 75%
“…Moreover, there is strong evidence that changes in the circulating metabolome and intestinal microbiota were closely associated with cardiovascular health status, and microbial and metabolomic profiling can be used to identify the crucial mechanisms responsible for the long-term outcomes [17, 18, 32]. Previous findings also suggested that high sodium intake could promote BP elevation by reducing the arachidonic acid and B fragilis levels in the intestine that could further increase the intestinal-derived corticosterone level in the serum and intestine [33]. However, previous Chinese epidemiologic studies were based on an observational design, which were not able to determine the causal relationship.…”
Section: Discussionmentioning
confidence: 99%